Herbal Medicine Practices of Patients With Liver Cancer in Peru: A Comprehensive Study Toward Integrative Cancer Management - Rojas Rojas, Teresa (2016)
The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: TRR was a recipient of a doctoral fellowship from Innóvate Perú (069-FINCyT-BDE-2014); JPC was a recipient of a doctoral fellowship from the Peruvian National Council for Science and Technology (212-2015-FONDECYT); ER and FD were supported by the Young Research Teams Associated with IRD Program (JEAI-INCAncer); and GB, PP, JG, ED, and SB were supported by the Third Cancer Plan of the French National Alliance for Life Sciences and Health (ENV201408).